An Intelligent Algorithm for Blood Cell Recognition Based on HHT-BPNN (Journal of Fiber Bioengineering and Informatics, 2015)
For the blood cell signal has the characteristics of nonlinear, non-stationary and M-morphous, an\rintelligent algorithm for blood cell recognition based on Hilbert-Huang Transformation and BP Neural\rNetwork (HHT-BPNN) is put forward, which convert the time domain features of the blood cell signal\rinto energy features by combining empirical mode decomposition with Hilbert transform, and put the\rtime domain features and the energy features together as the feature vector. Then, a model based on\rBP neural network is built by training and simulating that complete the work of effective identification\rand accurate count for M-morphous blood cells. Simulation results show that the algorithm proposed\rhas high recognition accuracy with good recognition performance.
Keywords: Blood Cell Recognition; Hilbert-Huang Transform (HHT); BP Neural Network; Empirical Mode Decomposition; Feature Vector